Effects of liver S9 enzymes on somalargine and solasodine cytotoxicity and mass spectrometric fragmentation - Ponsoni, Karina [UNESP]; Raddi, Maria Stella Gonçalves [UNESP]; de Almeida, Daniela V. [UNESP]; Almeida, Adelia Emilia de [UNESP]; Alécio, Alberto C. [UNESP] (Springer Nature, 2013)
The steroidal glycoalkaloid solamargine and its parent aglycone solasodine, isolated from Solanum palinacanthum, were studied in vitro for cytotoxicity and biotransformation by the hepatic S9 fraction as the metabolic activating system. The MTT uptake assay was used to determine viability after 24 h in RAW 264.7 mouse macrophage-like and SiHa cells exposed to various concentrations of the alkaloids in the presence and absence of the hepatic S9 microsomal fraction. The dose-response curves were established for solamargine and solasodine in the presence and absence of external metabolizing system. From these data, the cytotoxic index (CI50) was calculated with mean values of 7.2 and 13.6 μg/mL for Raw cells and 8.6 and 26.0 μg/mL for SiHa cells, respectively. Mass spectrometry was performed to compare the fragmentation patterns of the alkaloids to predict metabolism by the S9 fraction. The mass spectra demonstrated a distinct fragmentation patterns for solamargine and solasodine after the addition of the S9 fraction. In the present study, we demonstrate that the cytotoxic effect of solamargine and solasodine and their metabolites prepared in vitro by biotransformation with the S9 fraction are comparable. These findings suggest that the metabolic activation system S9 fraction may fail to suppress the cytotoxicity of these alkaloids. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Glycoalkaloid; Mass spectrometry; S9 fraction; Solamargine; Solasodine; Cytotoxic effects; Dose-response curves; Fragmentation patterns; Metabolic activation; Alkaloids; Chemical activation; Mass spectrometers; Metabolism; Metabolites; Nitrogen compounds; Cytotoxicity; Solanum; Solanum palinacanthum